Developing a Methodology for Analyzing the Risks of Bridge Construction Projects in Syria - سليم حسين; فايز جراد; رنا ميا (Latakia University Journal -Engineering Sciences Series, 2024)
The issue of risk management, which bridge construction projects are exposed to, has been the main concern of many studies around the world, because of the great importance of these projects, in addition to the possible impact that these projects may be exposed to due to risks in terms of cost, time, and quality. Therefore, the research aims to develop a methodology for analyzing the risks of bridge construction projects in Syria. The risks, which these projects are exposed to, are identified, then analyzed by using the method of Failure Mode and Effects Analysis (FMEA), which is combined with the fuzzy logic. Consequently, the probability of risks occurring, and their huge impacts on time, cost, and quality are determined, in addition to the possibility of detecting and controlling them. In the final stage, the risks are ranked according to their importance. The research has come out that the most significant risks in bridge construction projects are increased material prices, exchange rate changes, inflation, and unexpected site conditions.